Islam's view of science - Al-Qurashi, Amani Saud Khaishan (Journal of Arabic Language Sciences and Literature, 2025)
Islam has exploded scientific energies with its outlook free from forms of superstition and traditional ideas, and with its explicit call for research, observation, contemplation, and its understanding of the laws of the universe (its laws) - using the inductive and analytical method -; Therefore, it was not strange in Islamic civilization to find figures who were famous for their understanding of religion and their knowledge of other sciences, such as chemistry, mathematics, or astronomy.
Keywords: Exercising the mind; the scientific method; obtaining knowledge; astronomy; embryology and medicine; geography and natural phenomena; biology and the evolution of creatures